Effect of treatment with 5‐lipoxygenase inhibitor VIA‐2291 (atreleuton) on coronary plaque progression: a serial CT angiography study. Issue 4 (24th November 2016) - Matsumoto, Suguru; Ibrahim, Reda; Grégoire, Jean C.; L'Allier, Philippe L.; Pressacco, Josephine; Tardif, Jean‐Claude; Budoff, Matthew J.
Abstract : Background: Inflammation has a key role in the process of atherosclerosis. Production of leukotrienes by 5‐lipoxygenase has been linked to atherosclerotic plaques and cardiovascular events. Hypothesis: In this study, a selective 5‐LO inhibitor will slow plaque progression using serial cardiac computed tomographic angiography (CCTA). Methods: Patients with recent acute coronary syndrome (ACS) were prospectively assigned to one of 3 VIA‐2291 doses (25 mg, 50 mg, 100 mg) or placebo by oral administration. All groups underwent CCTA at baseline and at 6 months' follow‐up. Plaque types such as low‐attenuation plaque (LAP), fibro‐fatty tissue (FF), fibro‐calcified plaque (FC), and dense calcium plaque (DC) were measured based upon predefined density threshold, and changes from baseline CCTA were analyzed. Results: The final analysis included 54 patients (age, 56 ± 9 years; 85.1% male) with CCTA at baseline and 24 weeks. Evaluating on treatment VIA‐2291 (all 3 doses, n = 37) demonstrated significant reductions in plaque progression compared with placebo (n = 17). VIA‐2291 significantly reduced LAP (5.9 ± 20.7 mm 3 vs −9.7 ± 33.3 mm 3 ), FF (11.1 mm 3 ± 13.3 mm 3 vs −0.9 ± 2.7 mm 3 ), and FC (−0.1 ± 6.22 mm 3 vs −14.3 ± 6.2 mm 3 ; all P < 0.05) and retarded the progression of DC (3.9 ± 3.2 mm 3 vs 0.2 ± 0.4 mm 3 ) compared with placebo. Conclusions: VIA‐2291 resulted in slowed plaque progression compared with placebo across different plaque subtypes in patients with recent ACS (http://ClinicalTrials.gov NCT00358826).